Analysis of mechanisms of ensure the integrity and authenticity of the messages in MANET - Чевардін, Владислав Євгенійович; Ізофатов, Денис Олександрович (Ukrainian Information Security Research Journal, 2012)
Ensuring the integrity and authenticity of the messages in today's MANET networks is an urgent scientific and technical problem. The way to solve it is to conduct a continuous review of security threats of MANET, as well as the development and improvement of mechanisms of ensure the integrity and authenticity of information in the network. The analysis of the current attacks on the MANET networks and the corresponding threats of the integrity and authenticity of information has been done. The advantages and disadvantages of secure routing protocols are shown. As a result, identified promising areas of improvement and further development of security systems and secure routing protocols in MANET networks.